2018
DOI: 10.1007/s10898-018-0655-9
|View full text |Cite
|
Sign up to set email alerts
|

An abstract proximal point algorithm

Abstract: The proximal point algorithm is a widely used tool for solving a variety of convex optimization problems such as finding zeros of maximally monotone operators, fixed points of nonexpansive mappings, as well as minimizing convex functions. The algorithm works by applying successively so-called "resolvent" mappings associated to the original object that one aims to optimize. In this paper we abstract from the corresponding resolvents employed in these problems the natural notion of jointly firmly nonexpansive fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…This is what we do in Section 3. We mention that such a rate for a quite general uniformity condition (though not including the case examined here) was previously obtained in the paper [15].…”
Section: Introductionsupporting
confidence: 72%
“…This is what we do in Section 3. We mention that such a rate for a quite general uniformity condition (though not including the case examined here) was previously obtained in the paper [15].…”
Section: Introductionsupporting
confidence: 72%
“…Moreover, from this formulation given by (3) one immediately obtains, using (2), that a self-mapping of a CAT(0) space satisfying property (P 2 ) is nonexpansive. Following [34,48], if T and U are self-mappings of X and λ, µ > 0, we say that T and U are (λ, µ)-mutually firmly nonexpansive if for all x, y ∈ X and all α, β ∈…”
Section: Preliminariesmentioning
confidence: 99%
“…It is clear that a family (T γ ) is jointly firmly nonexpansive if and only if for every (γ n ) n∈N ⊆ (0, ∞), (T γn ) n∈N is jointly firmly nonexpansive with respect to (γ n ). In [34] it was shown that examples of jointly firmly nonexpansive families of mappings are furnished by resolvent-type mappings used in convex optimization -specifically, by:…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations